AFFECTIVITY IN EDUCATIONAL PRACTICE OF EARLY CHILDHOOD EDUCATION - Ferreira Favareto Cacheffo, Viviane Aparecida [UNESP]; Zauhy Garms, Gilza Maria [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
The qualitative research is characterized as a ethnographic case study, presented here, is linked to the research line Childhood and Education Program Graduate Education - MSc, Faculty of Science and Technology - FCT/UNESP and was performed during the years 2010-2012 - and have to investigate the conceptions of affectivity - emotion, feeling and passion - the teachers of a university daycare, and identify how they deal with affective expressions of children, seeking to give visibility to educational practices that promote child development. For the carrying out of the research, we have selected the following methodological tools: bibliographic search; documentary analysis; observation and semi-structured interviews, allowing the organization of data into five categories of analysis, which were analyzed by the Wallonian theory and revealed that the conceptions of affection and its manifestations are defined based on the relationship of interaction that teachers establish with children.
Keywords: Affectivity; Daycare; Early childhood Education Teacher